Patterns of corporate social responsibility of Ukrainian companies: clustering and improvement strategies for responsible activities - Sukhonos, Victor; Makarenko, Inna; Serpeninova, Yulia; Drebot, Oksana; Okabe, Yoshihiko (Problems and Perspectives in Management, 2019)
The variability of companies stakeholders’ engagement forms, communication channels, approaches to disclosure of companies’ corporate social responsibility (CSR) and strategies for CSR achievement cause the formation of benchmarks – patterns of responsible behavior of these companies. Determination of companies’ CSR patterns plays is a ground of (plays a role or is a ground of) improving their strategies for responsible activities. These patterns were highlighted on the basis of comprehensive three-component indicator that illustrates the combination of parameters: models of companies’ communication with stakeholders, approaches to the disclosure of information on CSR and strategies for incorporating CSR and Sustainable Development Goals. Positioning of 22 Ukrainian companies for the period 2005–2017 was made. Results of positioning allowed to determine such clusters of the companies in accordance with the pattern of responsible behavior as А – innovators, B – leaders, C – pursuer, D – followers, E – starters, F – outsiders; to develop the measures on the improvement of their CSR activity.